ANALYSIS AND SIMULATION OF CHEMICAL EXPLOSIONS IN NONSPHERICAL CAVITIES IN GRANITE - Stevens J.L.; Rimer N.; Xu H.; Murphy J.R.; Gibbons S.; Lindholm C.; Ringdal F.; Kvaerna T. (My University, 2006)
We analyze data from 15 decoupled chemical explosions conducted from 1986 to 2002 in Älvdalen, Sweden, recorded on regional seismic stations NORES, HFS, and NORSAR. The explosions were conducted in three approximately rectangular granite chambers at a depth of 100 m in chambers with volumes of 200, 300, and 1000 m3 and yields ranging from 500 to 10,000 kg. The smallest explosions in the largest chamber are fully decoupled, while the other explosions are partially coupled, overdriven by up to a factor of 25. The data show that decoupling remains fairly constant for overdrive up to about a factor of 10 then decreases rapidly at higher yields. Several 1000 kg explosions were conducted in the two smaller chambers. These events did not appear in seismic bulletins; however, we were able to identify the waveform and to estimate the origin time using a waveform correlation procedure. For the more recent explosions, near-field data were recorded on pressure gauges in the chamber and adjacent tunnel and on velocity gauges in boreholes at several locations near the chamber. We have modeled these data using three-dimensional finite difference calculations. The calculations show enhanced signals in the direction along the small axis of the chamber and reduced signals near the long end of the tunnel. Although we do not have free-field data from all directions, the data for the available locations are consistent with these calculations. Copyright 2006 by the American Geophysical Union.